2016
DOI: 10.1186/s12887-016-0717-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of invasive ventilation with neurally adjusted ventilatory assist (NAVA) in a crossover study

Abstract: BackgroundNeurally Adjusted Ventilatory Assist (NAVA) is a mode of assisted mechanical ventilation that delivers inspiratory pressure proportionally to the electrical activity of the diaphragm. To date, no pediatric study has focused on the effects of NAVA on hemodynamic parameters. This physiologic study with a randomized cross-over design compared hemodynamic parameters when NAVA or conventional ventilation (CV) was applied.MethodsAfter a baseline period, infants received NAVA and CV in a randomized order du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…One of the promising advantages of NAVA is the delivery of lower peak pressures compared to other modes of mechanical ventilation [4,6,8,10,17,18]. These previously reported studies have demonstrated that when changing from conventional ventilation to NAVA, the PIP decreases and there is a tendency towards decreased P aw [8,16,19].…”
Section: Discussionmentioning
confidence: 98%
“…One of the promising advantages of NAVA is the delivery of lower peak pressures compared to other modes of mechanical ventilation [4,6,8,10,17,18]. These previously reported studies have demonstrated that when changing from conventional ventilation to NAVA, the PIP decreases and there is a tendency towards decreased P aw [8,16,19].…”
Section: Discussionmentioning
confidence: 98%
“…Neurally Adjusted Ventilatory Assist (NAVA) and SIGH adjunct to PSV are two new modes of assisted ventilation that have been described in the last years in different pediatric setting, including postcardiosurgical patients . NAVA is a ventilatory mode that uses the electrical activity of the diaphragm (Eadi) to trigger, regulate, and cycle off the inspiratory pressure assistance; it has been shown to improve patient‐ventilator synchrony, to lower peak inspiratory pressure (PIP) and to accelerate the weaning process in one pediatric publication and to improve oxygenation as compared with PSV in one adult study . Conversely, a periodic “artificial recruiting breath” (SIGH) adjunct to PSV has been shown by our group to improve gas exchange and respiratory mechanics in postoperative (including cardiosurgical) ventilated children, without producing relevant complications in the short‐term .…”
Section: Introductionmentioning
confidence: 99%
“…In the abovementioned study [39], as in other studies [14,40], NAVA determined a significant reduction of peak inspiratory airway pressure and mean airway pressure when compared to conventional ventilation modes. In our study, peak inspiratory airway pressure was similar in all tested conditions, as we set the NAVA level to achieve similar peak inspiratory pressures to those observed during PSV.…”
Section: Discussionmentioning
confidence: 53%